DETERMINAN KEPATUHAN WAJIB PAJAK PADA WAJIB PAJAK PRIBADI DI DKI JAKARTA TAHUN 2022 - Steffi Jeannes Thomas; Ngadiman (Fakultas Ekonomi Universitas Tarumanagara, 2025)
The aim of the research is to test the influence of Tax Rates, Tax Socialization, and Tax System Effectiveness on Tax Compliance with Tax Awareness as a mediator. This research approach is quantitative. The population in this research is all individual taxpayers (WP) who live in DKI Jakarta Province. The sampling technique was carried out using purposive sampling. Data collection techniques are carried out through surveys. The research instrument used a closed questionnaire with a Likert scale of 1-6 (1=Strongly disagree, 6=Strongly agree). Data analysis techniques are descriptive analysis, multiple linear regression analysis, and path analysis, using SEM-PLS. The research results show that Tax Rates are proven to have a positive and significant effect on Tax Compliance, positive but not significant effect on tax awareness. Tax Socialization has a negative and insignificant effect on Tax Compliance. Tax Socialization has a positive and significant effect on Tax Awareness. The effectiveness of the Tax System has been proven to have a positive and significant effect on Tax Awareness and Tax Compliance. Tax Awareness has been proven to have a positive and significant effect on Tax Compliance. Tax Awareness can play a positive role in influencing the Effectiveness of the Tax System on Tax Compliance. However, Tax Awareness cannot play a positive role in the influence of Tax Tariffs/Duties on Tax Compliance, nor on the influence of Tax Socialization on Tax Compliance